The Role of Perceived Social and Spiritual Support and Depression to Health-related Quality of Life on Patients with SLE - Suci Nugraha; Elizabeth Kristi Poerwandari; Dharmayati Utoyo Lubis (Global Medical & Health Communication (GMHC), 2021)
Belief in the availability of social support (perceived social support) was known to influence depression and health-related quality of life in SLE patients. This support becomes a psychological resource when they experience negative emotional states such as depression caused by a chronic illness such as SLE. In people whose lives are influenced by religion, such as in Indonesian culture, belief in God's help (perceived spiritual support) is an important variable that needs to be studied because it is predicted to affect patients’ health-related quality of life. This study aims to explain the relationship between perceived social support, spiritual support, and depression to health-related quality of life in a patient with SLE. This cross-sectional study was conducted from March to June 2021 towards 328 SLE patients selected using the convenient sampling technique. Data was collected through forms that are distributed online and offline. The research sample was SLE patients who were members of a lupus community in Indonesia and lived in several cities in Java. The statistical analysis using a structural model (CMIN/df=103, RMSEA=0.103, CFI=0.972, TLI=0.963). Chi-square value=201,835 (p=0.000) suggested that perceived social support directly affected the level of depression and health-related quality of life on a patient with SLE, while perceived spiritual support affected the health-related quality of life through the mediation of depression, which means that spiritual support affected the quality of life by reducing negative emotions experienced by SLE patients. PERAN DUKUNGAN SOSIAL, SPIRITUAL, DAN DEPRESI TERHADAP KUALITAS HIDUP TERKAIT KESEHATAN PASIEN SLEKeyakinan akan ketersediaan dukungan sosial (perceived social support) diketahui memengaruhi depresi dan kualitas hidup terkait kesehatan pada pasien SLE. Dukungan ini diyakini menjadi sumber daya psikologis saat individu berada dalam kondisi emosi yang negatif seperti depresi yang disebabkan oleh penyakit kronis seperti SLE. Pada masyarakat yang kehidupannya dipengaruhi oleh agama seperti di Indonesia, keyakinan akan pertolongan Tuhan (perceived spiritual support) merupakan variabel penting yang perlu dipelajari karena diprediksi memengaruhi kualitas hidup terkait kesehatan. Penelitian ini bertujuan menjelaskan mekanisme hubungan antara perceived social support, spiritual support, dan depresi terhadap kualitas hidup terkait kesehatan pasien SLE. Penelitian cross-sectional ini dilakukan dari Maret hingga Juni 2021 pada 328 pasien SLE yang dipilih dengan convinient sampling technique. Data dikumpulkan melalui formulir yang disebarkan secara daring dan luring. Sampel penelitian merupakan pasien SLE yang tergabung dalam suatu komunitas lupus dan berdomisili di beberapa kota di pulau Jawa. Hasil analisis statistik dengan model struktural (CMIN/df=103; RMSEA=0,103; CFI=0,972; TLI=0,963). Nilai chi-square=201.835 (p=0,000) memperlihatkan bahwa perceived social support berpengaruh secara langsung pada tingkat depresi dan kualitas hidup pasien SLE. Sementara itu, perceived spiritual support memengaruhi kualitas hidup terkait kesehatan melalui mediasi depresi yang berarti bahwa spiritual support memengaruhi kualitas hidup dengan mengurangi kondisi emosi negatif yang dirasakan oleh pasien SLE.